Adaptation by coexistence: contrasting thermal comfort perception among individual and shared office spaces. (3rd July 2020) - Marín-Restrepo, Laura; Trebilcock, Maureen; Porras-Salazar, Jose Ali
ABSTRACT: Shared office spaces represent a challenge regarding thermal comfort. They have a diversity of occupants and expectations, and they require social interaction, which could imply restriction in adaptive actions, contrary to individual areas that usually allow total control. Hence, this paper aims to identify differences in thermal comfort criteria among individual and shared offices spaces by comparing adaptive opportunities and actions performed as well as thermal perception. Fieldwork was carried out in Chile in 18 office buildings, 9 in Concepcion (36°S), and 9 in Santiago (33°S). Thermal comfort surveys with simultaneous measurements of indoor environmental conditions were performed in each of these buildings during a single day in winter, spring and summer. The findings show variations in the criteria studied, which indicate that thermal requirements differ by spatial layout. Moreover, the results suggest that occupants of shared spaces have a wider comfort range; therefore, some kind of 'adaptation by coexistence' might be happening.